Critical Theory in Regressive Times: Liberalism, Global Populism and the “White Left” in the Twenty-First Century - Xingfu, Wang (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2019)
In this paper, I consider not only the crisis in conservative neoliberalism and free market economics, but a crisis of representation and plausibility in progressive new liberalism; a situation which leads to deadlock for progressivism in which things cannot progress. In order to address this state of crisis in the global perception of the “white left,” Critical Theory, as a mode of Western liberal thought, needs to rethink the direction of its own criticism. Additionally, Critical Theory needs to adjust its focus to respond to the deadlock presented by the rise of right-wing populism and the derogation of liberal values in these regressive times (I refer antonymically, here, to Jürgen Habermas’s use of the term “progressive”). The radical democratic ideal advocated by Habermas, comprising universal equality and emancipation, should still be the goal for liberalism, and for Critical Theory, but first of all, the achievements and advances liberal progressivism has already made need to be secured to prevent society from regressing. This does not mean making a choice between neoliberalism and authoritarianism, but that a new paradigm of thinking is due. I argue that universality is anterior to cultural pluralism, as are social topics to cultural issues, and justice of distribution to justice of identity. In the complex world of modernity, good things do not come together if there is conflict between desirable values, so choices need to be made: a ranking of real, material conditions is necessary, to ensure cohesion and progression.